Correlating the effects of ash elements and their association in the fuel matrix with the ash release during pulverized fuel combustion - Shah, Kalpit; Cieplik, M.; Betrand, C.; van de Kamp, W.; Vuthaluru, Hari (Elsevier, 2010)
During pulverized fuel combustion, inorganic elements such as alkalis, sulfur, chlorine, calcium and magnesium, as well as a range of minor elements are partly released into the gas phase. These gas-borne species can nucleate, coagulate and condense to form either aerosol particles or sticky layers on ash particles, leading to ash deposition and corrosion problems in power utilities. Furthermore, the fine aerosols can lead to harmful gaseous and particulate emissions. It is well documented that the mode of occurrence and the chemical speciation of ash forming elements in the coal/biomass structure are important for the release behavior of mineral components. In the presented work, this is investigated by performing quantitative elemental investigations of ash releases for two different coals (a Polish and a UK coal) and six diverse biomass fuels (Wood bark, Wood chips, Waste wood, Olive residue, Saw dust and Straw).The tests are performed within the Lab-scale Combustion Simulator (LCS) of the Energy Research Centre of the Netherlands (ECN). The operating conditions applied were that of a typical pulverized fuel (PF) fired boiler i.e. atmospheric pressure, high temperatures of 1400–1650 °C, and high heating rate of 105 K/s. Gas phase elemental release of alkalis, sulfur, chlorine, calcium and magnesium has been quantified at relevant high carbon conversion levels. With the performed set of experiments several of the past observations from the literature are reconfirmed. In addition to this, based on the extensive data pool at hand, a simple but reliable (R2 > 0.95) set of linear correlations have been proposed to predict the elemental release of potassium, sodium, chlorine and sulfur. It is also concluded that such linear expressions can be particularly effective for the prediction of elemental release from the fuels of similar characteristics, such as woody biomass.